Bridging infrastructure: Conceptualising non-state organisations in complex refugee settlement service landscapes. Issue 138 (January 2023) - Hewitt, Thea; Cook, Nicole
Abstract: This article conceptualises the work of non-state organisations in the refugee and migrant settlement sector with a focus on universal services, bureaucratic process and social dimensions of settling in a new country. In so doing it augments conceptualisations of 'social infrastructure', to encompass the social, emotional and administrative dimensions of social connection in diverse societies. Drawing on analysis of non-state organisations in the settlement services sector in Melbourne, Australia, we reveal the crucial work of organisations in developing programs and initiatives that recognise the complexity of mainstream welfare services, engage with the intangible social and emotional aspects of service provision, and that contribute to the accumulation of knowledge and expertise of complex and opaque services landscape. Moving beyond conceptualisations of social infrastructure as everyday community spaces, we introduce the concept of 'bridging infrastructure' to denote the work of organisations in interpersonal facilitation of social networks that enable access to wider services; the creation of friendly and welcoming community spaces; and the development of knowledge and expertise about a complex services landscape. Recognising the crucial role of the non-state sector in the dynamic process of humanitarian settlement, we contend that limited conceptualisations of social infrastructure risk removing 'the social' from bureaucratic and non-state services landscapes that support settlement lifeworlds.